2012
DOI: 10.1016/j.toxicon.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Nav channel blocking polypeptide from Cyanea capillata medusae – A neurotoxin contained in fishing tentacle isorhizas

Abstract: Jellyfish are efficient predators which prey on crabs, fish larvae, and small fish. Their venoms consist of various toxins including neurotoxins that paralyse prey organisms immediately. One possible mode of action of neurotoxins is the blockage of voltage-gated sodium (Na v) channels. A novel polypeptide with Na v channel blocking activity was isolated from the northern Scyphozoa Cyanea capillata (L., 1758). For that purpose, a bioactivity-guided multidimensional liquid chromatographic purification method has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Some fish also showed hyperactivity, jumping and occasional lateral convulsions consistent with potential neurotoxicity and loss of equilibrium. As C. capillata venom contains voltage‐gated sodium channel blocking neurotoxins (Lassen et al., ), this response would not be unexpected. However, for fish welfare reasons, the exposure was terminated after 2 hr.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some fish also showed hyperactivity, jumping and occasional lateral convulsions consistent with potential neurotoxicity and loss of equilibrium. As C. capillata venom contains voltage‐gated sodium channel blocking neurotoxins (Lassen et al., ), this response would not be unexpected. However, for fish welfare reasons, the exposure was terminated after 2 hr.…”
Section: Discussionmentioning
confidence: 89%
“…The gill cell toxicity of the venom from C. capillata and A. aurita has been examined in vitro using RTgill‐W1 cells (Helmholz, Johnston, Ruhnau, & Prange, ); however, these assays do not demonstrate the pathological effects on envenomated fish. As the venom mix from C. capillata has cytotoxic (Phospholipase A 2 ‐like activity; Helmholz, Ruhnau, Schütt, & Prange, ), neurotoxic (blocking Na v channels; Lasson, Weibring, Helmholz, Ruhnau, & Prange, ), hemolytic (CcTX‐1; Lassen, Helmholz, Ruhnau, & Prange, ) and systemic cardiovascular (Liang et al., ; Uvnäs, ; Wang et al., ) effects, the pathological responses of Atlantic salmon to envenomation are likely to involve a complex suite of pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that jellyfish venom consists of various bioactive substances, including cytolysins, neurotoxins, peptides and proteases [13, 20, 2628]. Unlike other venoms (snake, scorpion and spider), jellyfish venom is not secreted from venom glands or injected through specialized nematocysts that are present all over the cnidarians.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid sequences are available for some purified toxins (Brinkman et al, 2014;Lassen et al, 2011Lassen et al, , 2012Li et al, 2012). DNA and RNA sequencing have been conducted for Carukia barnesi, Malo kingi (Avila Soria, 2009), and Aurelia aurita.…”
Section: Venomicsmentioning
confidence: 99%